Un mausolée circulaire en contexte suburbain à Narbonne/Narbo Martius (Aude) - Olivier Ginouvez; Sandy Gualandi (Gallia)
The discovery of a circular monument during the rescue excavation of the Hôtel-Dieu in Narbonne, in 1996, allowed archaeologists to reassess the question of monumental funerary architecture in the capital of Narbonnaise Gaul. The foundations identified as those of a mausoleum were uncovered in the Southern Cemetery, near the via Domitia. The building is interpreted as a funerary monument in spite of the lack of certified rites. However, the location of the remains is in keeping with all the well-known criteria for this type of monument. Moreover, its architectural structure shows rare evidence of an original elevation. Thus, this discovery in Narbonne provides new data on circular mausoleums, which are still rare in Roman Gaul.